Whether Social Participation Can Affect the Central Government Public Policy Response to the COVID-19 in China - Fu, Liping; Sun, Huajun; Xu, Kaibo (Frontiers in Public Health, 2022)
Objective The coronavirus disease 2019 (COVID-19) outbreak has threatened the state's governance and public safety. This study investigates whether and how public participation can affect central government policy response to this pandemic in the context of China. Methods This study constructs the theoretical framework based on theoretical analysis, and Social Network Analysis is used to analyze data on the public participation, New Media, and the central government response in this pandemic. Results Findings show that the Chinese central government does not always adopt top-down elitist governance strategies in risk management. The central government will also adopt the bottom-up governance strategy triggered by public participation. In this process, New Media acts as a catalyst. Specifically, when faced with a public emergency and needs a policy response from the central government, public participation firstly creates “participation” with the authority of the media, forms public opinion, and then the prompt policy response from the central government. Conclusion This study confirms that the central government will refer to public participation to decide the policy response. It also shows that the theory of government response applies to both the local government and the central government.